2011
DOI: 10.1038/emboj.2011.391
|View full text |Cite
|
Sign up to set email alerts
|

Signal-dependent incorporation of MyoD-BAF60c into Brg1-based SWI/SNF chromatin-remodelling complex

Abstract: Tissue-specific transcriptional activators initiate differentiation towards specialized cell types by inducing chromatin modifications permissive for transcription at target loci, through the recruitment of SWItch/Sucrose NonFermentable (SWI/SNF) chromatin-remodelling complex. However, the molecular mechanism that regulates SWI/ SNF nuclear distribution in response to differentiation signals is unknown. We show that the muscle determination factor MyoD and the SWI/SNF subunit BAF60c interact on the regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
240
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(250 citation statements)
references
References 59 publications
5
240
0
1
Order By: Relevance
“…More recently, Imbalzano's laboratory has exploited RNAi to knock down the levels of Brg1, showing that Brg1 controls muscle genes and muscle-specific microRNAs (myomiRs) expression in skeletal muscle cells [24]. Likewise, we have shown by RNAi-mediated knockdown the essential role of Brg1/BAF60C-based SWI/SNF complex in the activation of the myogenic program in C2C12 muscle cells [25]. Still, the specific function of Brm in skeletal myogenesis remains obscure to date.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…More recently, Imbalzano's laboratory has exploited RNAi to knock down the levels of Brg1, showing that Brg1 controls muscle genes and muscle-specific microRNAs (myomiRs) expression in skeletal muscle cells [24]. Likewise, we have shown by RNAi-mediated knockdown the essential role of Brg1/BAF60C-based SWI/SNF complex in the activation of the myogenic program in C2C12 muscle cells [25]. Still, the specific function of Brm in skeletal myogenesis remains obscure to date.…”
Section: Introductionmentioning
confidence: 71%
“…Previous studies showed that Brg1 is required for the activation of myogenin expression during skeletal myogenesis [6,22,25]. Genetic and molecular studies have established that myogenin expression at early stages of skeletal myogenesis establishes a key restriction point for the activation of the differentiation program in skeletal myoblasts [37][38][39].…”
Section: Brm But Not Brg1 Is Required For the Completion Of Muscle DImentioning
confidence: 99%
“…In mammals, different alternative variants of SWP73/BAF60 SWI/SNF subunits have been uncovered to play major roles in tissue-specific regulation of gene expression (Takeuchi and Bruneau, 2009;Forcales et al, 2012). Detailed functional characterization of the two Arabidopsis SWP73 homologs has been so far handicapped due to lack of suitable null mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The BAF60c-MyoD complex is identified in chromatin regions of MyoD target genes, and genetic studies indicate that BAF60c enables MyoD to access its target sites in repressive chromatin of undifferentiated myoblasts. Next, likely an extracellular differentiation stimulus triggers the recruitment of catalytic and core subunits of SWI/ SNF to the BAF60c-MyoD "pioneer complex," stimulating nucleosome remodeling (Albini et al, 2013), which is, in turn, dependent on phosphorylation of the BAF60c Thr-229 residue by the differentiation-activated p38a kinase (Forcales et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] In particular, studies from Saccone et al have identified an HDAC-regulated network that controls the functional phenotype of FAPs from dystrophic muscles. Treatment with HDACi promotes the expression of two core components of the myogenic transcriptional machinery, MyoD and BAF60c [15] and upregulates three myogenic microRNA involved into muscle differentiation (myomiRs; miR-1.2, miR-133 and miR-206) in FAPs. MyomiRs in turn target two alternative BAF60 variants -BAF60 A and B -that when incorporated into the Switch/Sucrose NonFermentable (SWI/SNF) chromatin-remodeling complex would otherwise promote the activation of the fibro-adipogenic program.…”
Section: Hdac Inhibitors For Muscular Dystrophies: Progress and Prospmentioning
confidence: 99%